Historical blocking: CN 2020-04-23 (China) - Voidly (2020)
CRITICAL severity censorship detected in China. Confidence: 97%. Data sourced from ooni-historical-backfill.
Censorship Incident ID: CN-2020-0002
Keywords: censorship; CN; censorship; critical